The divergence of school track choices after Covid-19 - Philipp Breidenbach; Lukas Hörnig; Sandra Schaffner (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
During the pandemic, many measures were taken to prevent the spread of Covid-19. Some of these measures, such as school closures, directly affected students. Children from different backgrounds are likely to have different abilities to cope with the challenges of the pandemic and associated countermeasures. We analyse whether pre-existing differences in transition rates from primary schools in low-income and high-income neighborhoods to secondary schools have widened. Our results show that the transition rate from primary schools to Gymnasium, the academic track, increased by 1.5 percentage points in primary schools in high-income neighborhoods compared to primary schools in low-income neighborhoods, suggesting that the pandemic increased educational differences in Germany. We provide suggestive evidence that children's technological equipment and parents' capabilities to help their children differ across neighborhood types. – – Während der Pandemie wurden zahlreiche Maßnahmen ergriffen, um die Ausbreitung von Covid-19 zu verhindern. Einige dieser Maßnahmen, wie z. B. die Schließung von Schulen, betrafen die Schüler direkt. Kinder mit unterschiedlichem Hintergrund haben wahrscheinlich unterschiedliche Möglichkeiten, mit den Herausforderungen der Pandemie umzugehen. Wir untersuchen, ob sich die bereits bestehenden Unterschiede bei den Übergangsquoten von Grundschulen in einkommensschwachen und einkommensstarken Nachbarschaften auf weiterführende Schulen vergrößert haben. Unsere Ergebnisse zeigen, dass die Übergangsrate von der Grundschule zum Gymnasium in Grundschulen in einkommensstarken Vierteln um 1,5 Prozentpunkte höher war als in Grundschulen in einkommensschwachen Vierteln, was darauf hindeutet, dass die Pandemie die Bildungsunterschiede in Deutschland verstärkt hat. Wir zeigen aus nicht-repräsentativen Umfragedaten, dass sich die technische Ausstattung der Kinder und die Möglichkeiten der Eltern, ihre Kinder zu unterstützen, je nach Wohngegend unterscheiden.
Keywords: I24; I21; J15; D30; 330; Covid-19; school closures; educational inequality; school tracking; neighborhood effects